2005
DOI: 10.1021/ie048972t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silicalite Membranes on Stainless Steel Grid Supports

Abstract: Silicalite membranes have been prepared by seeded liquid-phase hydrothermal synthesis on alternative supports, namely, two types of stainless steel grids with opening sizes ranging from 2 to 5 µm. The influence of the gel composition, the use of surfactants, and the synthesis time have been studied. The silicalite membranes prepared on stainless steel grids were tested in the separation of n-/i-butane mixtures, showing performances which are comparable to those of good quality membranes prepared on conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…12 Zeolite membranes can be produced by hydrothermal crystallization of specific zeolite films, typically of the FAU, MFI and DDR type, onto various types of porous supports, e.g. stainless steel, 13 a and g alumina, 14,15 clay, 16 cordierite, 17 glass 18 and carbon. 19 Some zeolite membranes have been introduced commercially, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…12 Zeolite membranes can be produced by hydrothermal crystallization of specific zeolite films, typically of the FAU, MFI and DDR type, onto various types of porous supports, e.g. stainless steel, 13 a and g alumina, 14,15 clay, 16 cordierite, 17 glass 18 and carbon. 19 Some zeolite membranes have been introduced commercially, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) and silicalite, pure and multilayer composite membranes were synthesized on 316 L porous stainless steel disks (Mott Corp., diameter = 5.6 cm, thickness = 0.039 in, average pore size = 2 µm). Before coating, the supports were treated with water and acetone in an ultrasonic bath . PDMS membranes were prepared from RTV615A and RTV615B (Momentive Performance Materials) by spin‐coating at 1000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Membrane synthesized by both techniques, i.e. in situ direct synthesis and secondary growth, and the residual powder collected at the bottom of the autoclave after the synthesis were washed with distilled water until pH 7, and dried at 80 °C for 24 h. The template in the silicalite pores was removed by heating to 470 ° C for 4 h at a heating rate of 0.3 °C min −1 and a cooling rate of 5 °C min −1 . Multilayer composite membranes were prepared by coating silicalite membranes with PDMS solution by spin‐coating at 1000 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations have suggested that using FAU, CO 2 /N 2 separation with selectivity exceeding 500 and with CO 2 permeability of 10 000 barrer (1 barrer = 3.35 × 10 –16 mol m/(m 2 s Pa), permeance units are expressed in GPU, with barrer and GPU being the same for a 1 μm membrane) can be achieved . Extensive research is being carried out on zeolite membranes, with development of novel ways to deposit zeolites on supports . Growth of zeolite crystals within the pores of alumina supports, a method referred to as pore plugging, and gas separation properties with such materials have also been reported. Polymer supports are also being used for zeolite membranes .…”
Section: Introductionmentioning
confidence: 99%